2006
DOI: 10.1104/pp.106.084319
|View full text |Cite
|
Sign up to set email alerts
|

The TATA-Box Sequence in the Basal Promoter Contributes to Determining Light-Dependent Gene Expression in Plants

Abstract: A prototype 13-bp TATA-box sequence, TCACTATATATAG, was mutated at each nucleotide position and examined for its function in the core promoter. Specific nucleotides in the first TATA, the second TATA, as well as the flanking sequences influenced promoter function in transient transformation of tobacco (Nicotiana tabacum var Petit Havana) leaves. The effect of a given mutation on reporter gene expression in light versus dark was variable and sometimes contrasting. Some mutations, like T 7 or A 8 /C or G, comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…In an earlier work (Kiran et al, 2006), we had demonstrated the critical role that nucleotides at the seventh and eighth positions play in the consensus TATA-box TCACTATATATAG for light-mediated transcription, both in the presence and absence of the 52-bp lre (Martinez-Hernandez et al, 2002). This study investigates the role of the ninth nucleotide in expression from the same prototype minimal promoter (Pmec) containing TCACTATATATAG as a consensus TATA-box (Supplemental Fig.…”
Section: Substitution Of G/c At the Ninth Position In The Consensus Tmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier work (Kiran et al, 2006), we had demonstrated the critical role that nucleotides at the seventh and eighth positions play in the consensus TATA-box TCACTATATATAG for light-mediated transcription, both in the presence and absence of the 52-bp lre (Martinez-Hernandez et al, 2002). This study investigates the role of the ninth nucleotide in expression from the same prototype minimal promoter (Pmec) containing TCACTATATATAG as a consensus TATA-box (Supplemental Fig.…”
Section: Substitution Of G/c At the Ninth Position In The Consensus Tmentioning
confidence: 99%
“…TFIID is a multisubunit protein complex consisting of TBP and approximately 14 associated factors that plays a critical role not only in promoter binding but also as a transducer in conveying the upstream regulating signals to the downstream general transcription machinery. The core promoter and its elements are highly variable, so they can be a point of regulation for gene-specific transcription (Zhu et al, 1995;Nakamura et al, 2002;Kiran et al, 2006;Bjornsdottir and Myers, 2008). Efficient transcription generally requires the synergistic action of multiple activators bound at distinct sites upstream (or downstream) of the promoter (Struhl, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of cis-elements have been identified from varied species that have been shown to involving responding to stimuli of light, signal molecule and invading bacteria [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the G-box variant 3 was relatively close of a 5'-TATAAA-3' sequence, positions -153 (pYUC8) and -267 (pYUC9). This sequence was identified as the consensus TATA-box, which is commonly recognized as a transcription enhancer (Kiran et al 2006). …”
mentioning
confidence: 99%